Dinamika Penolakan Penjabat Kepala Daerah Dari Pusat di Kalimantan Tengah Dalam Perspektif Politik Hukum - Dewi, Vina Fajar; Daim, Nuryanto Ahmad (Law and Humanity, 2023)
The dynamics of rejection of the Acting Regional Head in Central Kalimantan, namely Acting. South Barito Regent and Acting. West Kotawaringin had caught the attention of the public in Central Kalimantan. This is none other than because the Governor, based on suggestions from the public, has submitted several suggestions for names of local sons who will occupy these positions. However, as a result, the Central Government decided to drop the name as Acting. South Barito Regent and Acting. Regent of West Kotawaringin. This event is interesting to study in the perspective of legal politics. This study was conducted using a normative legal approach that uses data sources from positive law supported by several references in print and online media. The results of the study show that the dynamics of resistance that occurred at that time lasted very briefly and the central government showed dominance in the appointment and appointment of acting regents. This will certainly be a record for the local people of Central Kalimantan that the spirit of democracy has been harmed by the Central Government. Community participation and proposals only apply as accessories in the current government's legal politics.